EXCAVATION OF DERBENT SETTLEMENT IN 2017 - Gadziev, Murtazali Serazutdinovic; Budajciev, Arsen Lahmanovic; Abdulaev, Abdula Magomedovic; Abiev, Askerhan Kamalovic (History, Archeology and Ethnography of the Caucasus, 2020)
The article is dedicated to the results of 2017 season excavations of Derbent settlement which existed before construction of the Derbent defensive complex at the end of 560-s. This settlement was gradually left after the construction of a new city given the new name Derbent (Darband). The cultural layers and the construction remains (rooms 6, 7, 8, 9) of the 5-th – 6-th centuries AD, the medieval Muslim burials which have been dug in the layer of the settlement were open in the southern sector of the excavation area XXV.The revealed complex of inhabited and economic constructions including 9 rooms is dated the 5th century AD on the basis of chronological indicators (bronze belt buckles, fibula) and other archeological finds (including, Sasanian pottery). Authors consider that this complex has stopped existence during the military-political events of the middle of the 5th century or of the beginning of the 6th century, namely in the period of an anti-Sasanian revolt of 450-451 or Iran-Savir war of 503-508 AD.The materials obtained during excavations shed new light on issues of historical topography and layout, stratigraphy and chronology, architecture and construction, economic activity, culture and life of the inhabitants of the Derbent settlement which is identified with the city-fortress of Chor/Chol known for ancient Armenian, Georgian, Syrian, Early Byzantine and Arab authors and which was the important administrative, military and religious center of East Caucasus. The received materials characterize culture.
Keywords: Derbent; Chor; settlement; Late Antiquity; Early Medieval times; Sasanian pottery.